Transitions to and from at-risk alcohol use in adults in the United States. (2nd January 2019) - Saitz, Richard; Heeren, Timothy C.; Zha, Wenxing; Hingson, Ralph
ABSTRACT: Introduction: The objective of this research is to study transitions to and from at-risk alcohol use. Methods: Logistic regression analyses (done 2015–2016) assessed transitions to and from past-year at-risk drinking in a representative sample of U.S. adults surveyed twice (in 2001–2002 and 2004–2005). Results: Among 34, 653 adults, 28% reported at-risk use at time 1. Of those, 73% had at-risk use at time 2. Of those without at-risk use at time 1, 15% reported at-risk use at time 2. Positive high-risk drinking transition predictors were, at time 1, being young, male, white, childless, in good to excellent health, ever smoking, using drugs, military membership (time 1 but not 2), and becoming divorced or separated by time 2. Positive low-risk drinking transition predictors were being elderly (age ≥ 65), female, non-white, never smoking or using drugs, no alcohol use disorder, alcohol treatment, and, after time 1, having children. Conclusions: Many adults transition to and from at-risk alcohol use; youth is the strongest positive predictor of transition to at-risk and not transitioning to low-risk drinking. Persons transitioning to legal drinking age are most likely to transition to high-risk and least likely to low-risk drinking.